Reconfiguration of distribution networks with simultaneous allocation of distributed generation using the whale optimization algorithm - Mahdavi, Elham [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Due to the economic interest of the reduction of the power losses and the regulatory requirements regarding voltage levels in steady state, this study offers a computational methodology to assist in the optimization of the power losses and voltage profile in steady state through the distribution network reconfiguration (DNR) and distributed generations (DGs). The power flow execution and the methods of the sophisticated optimization are able to investigate the big combinative problems required to study DNR. The optimization procedure kind utilized in the distribution network is determined based on the size of the network. Approaches that are expensive in terms of computation or prohibitive include direct approaches, but approaches that have acceptable results with less computational expense include heuristic or metaheuristic approaches. In this research, the load flow that is implemented, is the backward-forward sweep method and we intend to use IEEE 33-bus, IEEE 69-bus, 136-bus, and 415-bus systems. Therefore, we consider the simulation of all the systems according to the network layout and proper placement of DGs in the network using the whale optimization algorithm (WOA). The objective function is to reduce power losses by the DNR and the optimal location and size of DG units, but the voltage profile also improves in this problem. Due to the nonlinear, nonconvex and large nature of the problem, the WOA is used to optimize the problem under MATLAB software. The results indicate that the WOA algorithm performs better in terms of power loss reduction and voltage profile improvement when compared with other metaheuristics shown in the chapter of the tests and results.

Devido ao interesse econômico da redução das perdas de potência e aos requisitos regulatórios referentes aos níveis de tensão em regime permanente, este trabalho propõe uma metodologia computacional para auxiliar na otimização das perdas de potência e perfil de tensão em regime permanente através da reconfiguração da rede de distribuição (RRD) e Gerações Distribuídas (GDs). A execução do fluxo de potência e os métodos de otimização sofisticados são capazes de investigar os grandes problemas combinatórias necessários para estudar o RRD. O tipo de procedimento de otimização utilizado na rede de distribuição é determinado com base no tamanho da rede. Abordagens que são caras em termos de computação ou proibitivas incluem abordagens diretas, mas abordagens que têm resultados aceitáveis com menor gasto computacional incluem abordagens heurísticas ou metaheurísticas. Nesta pesquisa, o fluxo de carga implementado é o método backward-forward e são usados os dados dos sistemas de IEEE 33 barras, IEEE 69 barras, 136 barras e 415 barras. Portanto, consideramos a simulação de todos os sistemas de acordo com o tipo de rede e o posicionamento adequado dos GDs na rede usando o algoritmo de otimização de baleias (AOB). A função objetivo é minimizar a perdas de potência pelo RRD e a localização e tamanho ideais das unidades GD, mas o perfil de tensão também melhora neste problema. Devido à natureza não linear, não convexa e grande porte do problema, o AOB é usado para otimizar o problema usando o software MATLAB. Os resultados indicam que o algoritmo AOB apresenta melhor desempenho em termos de redução de perdas de potência e melhora do perfil de tensão quando comparado com outras metaheurísticas mostradas no capítulo de testes e resultados.
Reconfiguração de redes de distribuição com alocação simultânea de geração distribuída usando o algoritmo de otimização baleia
Keywords: Whale optimization algorithm; Distribution network; Reconfiguration; Power losses; Distributed generation; MATLAB; Algoritmo de otimização de baleias; Rede de distribuição; Reconfiguração; Perdas de potência; Geração distribuída